2013
DOI: 10.1177/1049732313507502
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Experiences of Hearing Voices and Sounds Others Do Not Hear

Abstract: In this article, we aim to contribute to the understanding of how people with mental illness experience hearing voices and sounds that others do not hear in daily life. We conducted in-depth interviews with 14 people and analyzed the interviews using a hermeneutic phenomenological approach. The themes we arrived at included the following: hearing someone else or myself, am I losing my mind?, and daily life recurrently dominated by opposing voices. Our overall understanding of how the voices and sounds were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 42 publications
1
23
0
3
Order By: Relevance
“…Participant (9) reported that "voices always call me by bad names such as ……stupid …….. ugly, and loser". Participant (6) stated that voices "whisper to me about other people around me………warning me that bad people will hurt me, stay away from these people".…”
Section: ) Voices Have Harmful Unpleasant Naturementioning
confidence: 99%
See 2 more Smart Citations
“…Participant (9) reported that "voices always call me by bad names such as ……stupid …….. ugly, and loser". Participant (6) stated that voices "whisper to me about other people around me………warning me that bad people will hurt me, stay away from these people".…”
Section: ) Voices Have Harmful Unpleasant Naturementioning
confidence: 99%
“…pray", Participant (6) said "I usually read Quran …… (the holy book of Islam) to make the voices stay away from me and it works". Participant (9) said that sometimes I stay with people around me …….. the voices do not come". Participant (5) reported that, "I hear the voices …….. try to forget what they say …….I do not pay much of attention to what they say".…”
Section: ) Different Ways For Dealing With Auditory Hallucinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon is associated with educational difficulties, diminished ability to work, and suicidal behavior (Harkavy-Friedman et al, 2003; Kalhovde, Elstad & Talseth, 2013). Experiences of hearing voices, commonly known as auditory (verbal) hallucinations, are regarded as a hallmark symptom of serious mental illness in Western cultures.…”
mentioning
confidence: 99%
“…This has significant therapeutic value and can help nurses to build the skills and confidence to collaborate with consumer to explore what the voices they hear 'echo and amplify'. Kalhovde et al (2013) and Martins (2008) showed that using phenomenology influences the types of research questions asked and the forms of knowledge generated. As phenomenology is the study of the perceptions of people experiencing a phenomenon rather than the empirical study of the phenomenon itself (Giorgi 1997), it is highly appropriate for exploring the experiences of people with mental illness and how they consciously reflect on those experiences.…”
Section: Applying a Phenomenological Approachmentioning
confidence: 99%